2017
DOI: 10.1002/2016gl072201
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varying extreme rainfall intensity‐duration‐frequency curves in a changing climate

Abstract: Anthropogenic climate change influences the nature and probabilistic behavior of extreme climate phenomena over time. Current infrastructure design of water systems, however, is based on intensity‐duration‐frequency (IDF) curves that assume extreme precipitation will not significantly change. To sustain the reliability of infrastructure designs in a changing environment, time‐varying nonstationary‐based IDF curves must replace the static stationary‐based IDF curves. This study outlines a fully time varying ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…Nevertheless, the methodology to derive existing IDF curves has certain drawbacks, for example that the current IDF curves in Canada are based on the assumption of stationarity, which implies that statistical properties of hydroclimatic time series will remain the same over the period of time. However, the impact of urbanization and humaninduced climate change (IPCC SREX, 2012;Villarini et al, 2009a;Milly et al, 2009;Kunkel, 2003) raises the question of whether the stationarity assumption to derive IDF curves is still reliable for urban infrastructural planning (Sarhadi and Soulis, 2017;Cheng and AghaKouchak, 2014;Jakob, 2013;Yilmaz et al, 2014a;Yilmaz and Perera, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the methodology to derive existing IDF curves has certain drawbacks, for example that the current IDF curves in Canada are based on the assumption of stationarity, which implies that statistical properties of hydroclimatic time series will remain the same over the period of time. However, the impact of urbanization and humaninduced climate change (IPCC SREX, 2012;Villarini et al, 2009a;Milly et al, 2009;Kunkel, 2003) raises the question of whether the stationarity assumption to derive IDF curves is still reliable for urban infrastructural planning (Sarhadi and Soulis, 2017;Cheng and AghaKouchak, 2014;Jakob, 2013;Yilmaz et al, 2014a;Yilmaz and Perera, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The RAMK test indicates that trends are 25 statistically positive for 15-, 30-, and 1440-minute durations. The lack of a clear signal in the direction of the trends has been previously reported for other regions (Sarhadi and Soulis, 2017) and might be linked to the weak power of statistical methods when the data are affected by high natural variability as is the case of precipitation (Renard et al, 2008).…”
Section: Trend Analysis Of Precipitation Extremesmentioning
confidence: 92%
“…In addition, positive increases in observed precipitation linked to a warmer atmosphere also bring into question the validity of the IDF curves developed under stationary assumptions and has prompted the development of new methods for determining return periods and risk that take 20 into account the effect of non-stationary in climate extremes (Bhatkoti et al, 2016;Condon et al, 2015;Du et al, 2015;Khaliq et al, 2006;Obeysekera and Salas, 2014;Salas and Obeysekera, 2014;Serinaldi and Kilsby, 2015). A few climate studies have shown that design storm estimates from stationary models are significantly lower than estimates from nonstationary models (Cheng and AghaKouchak, 2014;Sarhadi and Soulis, 2017;Wi et al, 2016). However, the lack of observed sub-daily precipitation limits the studies to using scaling factors to temporally disaggregate daily observations or 25 use merged radar-rain gauge data (Cheng and AghaKouchak, 2014;Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cheng and AghaKouchak [78] employed a nonstationary GEV distribution with a time-varying location parameter to model a nonstationary IDF curve. They fitted the nonstationary GEV distribution for each duration examined, and their study provided an IDF curve for extreme rainfall events in the U.S. Sarhadi and Soulis [79] modeled a nonstationary IDF curve using the nonstationary GEV distribution with time-varying location and scale parameters. However, the temporal structure of the extreme rainfall events of South Korea change, although there is no trend in the mean of extreme rainfall events.…”
Section: Characteristics Of Spatial and Temporal Structure Of Extremementioning
confidence: 99%